Mineral Element Stocks in the Yedoma Domain: A Novel Method Applied to Ice-Rich Permafrost Regions - Monhonval, Arthur; Mauclet, Elisabeth; Pereira, Benoît; Vandeuren, Aubry; Strauss, Jens; Grosse, Guido; Schirrmeister, Lutz; Fuchs, Matthias; Kuhry, Peter; Opfergelt, Sophie (Frontiers in Earth Science, 2021)
With permafrost thaw, significant amounts of organic carbon (OC) previously stored in frozen deposits are unlocked and become potentially available for microbial mineralization. This is particularly the case in ice-rich regions such as the Yedoma domain. Excess ground ice degradation exposes deep sediments and their OC stocks, but also mineral elements, to biogeochemical processes. Interactions of mineral elements and OC play a crucial role for OC stabilization and the fate of OC upon thaw, and thus regulate carbon dioxide and methane emissions. In addition, some mineral elements are limiting nutrients for plant growth or microbial metabolic activity. A large ongoing effort is to quantify OC stocks and their lability in permafrost regions, but the influence of mineral elements on the fate of OC or on biogeochemical nutrient cycles has received less attention and there is an overall lack of mineral element content analyses for permafrost sediments. Here, we combine portable X-ray fluorescence (pXRF) with a bootstrapping technique to provide (i) the first large-scale Yedoma domain Mineral Concentrations Assessment (YMCA) dataset, and (ii) estimates of mineral element stocks in never thawed (since deposition) ice-rich Yedoma permafrost and previously thawed and partly refrozen Alas deposits. The pXRF method for mineral element quantification is non-destructive and offers a complement to the classical dissolution and measurement by optical emission spectrometry (ICP-OES) in solution. Using this method, mineral element concentrations (Si, Al, Fe, Ca, K, Ti, Mn, Zn, Sr and Zr) were assessed on 1292 sediment samples from the Yedoma domain with lower analytical effort and lower costs relative to the ICP-OES method. The pXRF measured concentrations were calibrated using alkaline fusion and ICP-OES measurements on a subset of 144 samples (R² from 0.725 to 0.996). The results highlight that (i) the most abundant mineral element in sediments of the Yedoma domain (1 387 000 km²) is Si (2739 ± 986 Gt) followed by Al, Fe, K, Ca, Ti, Mn, Zr, Sr, and Zn, and that (ii) Al and Fe (598 ± 213 and 288 ± 104 Gt) are present in the same order of magnitude as OC (327-466 Gt).